RFID based indoor localization for autonomous guided vehicles application and management panel - KIYAK, İSMAİL (My University, 2023)
Today, especially since 2020, after the Covid-19 pandemic, intensive cargo transportation has made a breakthrough regardless of large or small scale. Especially during the pandemic period, people frequently shopped on e-commerce websites, causing a serious logistics business volume here. Logistics companies had difficulty in responding to this density and went to different solutions. These have created various business volumes, especially in the field of indust- rial automation. In this thesis, it is aimed to design a low-cost RFID-based autonomous guided vehicle design and management panel that can respond to the problem of in-house product distribution speed of small-scale enterprises, which can systematically track and distribute products in warehouses. A simulation of the product to be implemented in this project has been made. A 1:5 scale prototype of the product to be used in real life was prepared and studies were carried out. The vehicle included RFID receiver, accelerometer/gyro sensor (IMU), stepper motor, stepper motor dri- ver, microprocessor (MCU) and PC throughout the work. The shortest path algorithm developed within the scope of the study was carried out in order for the vehicle to perform the tasks given at the optimum speed within the area determined here.
Keywords: Autonomous Guided Vehicles; Autonomy; Differential Drive; Motion Control; RFID